Taraxacum gilliesii Hook. & Am. (Asteraceae), new record for it distribution area in Argentina (Semiárida, 2020)
Taraxacum gilliesii Hook. & Arn. (Asteraceae) is reported for La Pampa province expanding its distribution area in Argentina. A key is supplied for distinguish from T. officinale F. H. Wigg. present too in this province.
Keywords: New record; Taraxacum gilliesii; Taraxacum officinale; La Pampa; Flora